Ruth St. Denis play scripts - St. Denis, Ruth, 1880-1968.
Typescript for a play entiled Egypta (undated) and printed version of the script for Radha, An East Indian Idyl, submitted for copyright in 1905.
Dancer and playwright. Also known as Ruth Dennis. Married Ted Shawn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: American drama; Drama -- Stories, plots, etc; Dancers; Playwrights